2023
DOI: 10.3389/fpubh.2023.1251828
|View full text |Cite
|
Sign up to set email alerts
|

Blood donation practice and its associated factors among Polish population: secondary data analysis

Barbara Siekierska,
Lucyna Tomaszek,
Paulina Kurleto
et al.

Abstract: IntroductionBlood transfusion is an intervention widely used in therapeutics (e.g., in the perioperative period), thus, knowledge about factors associated with blood donation is important. The aim of this study was to investigate the impact of sociodemographic factors, personal values and life satisfaction on blood donation in Poland.MethodsSecondary analysis of data. A multiple logistic regression was carried out to assess the relationship between sociodemographic factors, life satisfaction (Satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Notably, university students exhibit a higher blood donation rate compared to college students, consistent with existing research highlighting the correlation between higher education levels and increased likelihood of blood donation [ 32 ]. In a similar vein, elevated education levels tend to heighten awareness of blood donation, thereby promoting donation behavior [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, university students exhibit a higher blood donation rate compared to college students, consistent with existing research highlighting the correlation between higher education levels and increased likelihood of blood donation [ 32 ]. In a similar vein, elevated education levels tend to heighten awareness of blood donation, thereby promoting donation behavior [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…This trend may be attributed to females’ typically stronger empathy than males, motivating them toward blood donation [ 10 ]. Conversely, other findings suggest a lower blood donation rate among older females compared to males, potentially due to the challenges females face in donation eligibility stemming from childbirth and family responsibilities [ 30 32 ]. Furthermore, our study’s outcomes diverge from those in Qatar and Saudi Arabia, where religious constraints impede female blood donation [ 3 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood donation projections from the study have some clinical implications. Some previous studies have shown that the survival rate of patients transfused with blood from male donors was higher compared to female donors [ 41 ]. Therefore, the higher proportion of male donors in the pool is vital in clinical blood transfusion.…”
Section: Discussionmentioning
confidence: 99%